Conductive paint and circuit forming body

CN119013358BActive Publication Date: 2026-10-30FUJIKURA KASEI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380035651.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-04-27
Filing Date
2023-04-21
Publication Date
2026-10-30
Estimated Expiration
2043-04-21

AI Technical Summary

Benefits of technology

[0034]根据本发明,能够提供一种导电性涂料,所述导电性涂料能够形成即使反复伸缩耐久性仍优异且电阻值的变化率小的涂膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119013358B_ABST
    Figure CN119013358B_ABST
Patent Text Reader

Abstract

The present application is a kind of conductive paint, the conductive paint of the present application includes silicone resin (A) and conductive powder (B) with specific mass ratio, the conductive powder (B) includes flaky conductive powder (B1) with average particle size of 1-7 μm, amorphous conductive powder (B2) with average particle size of 1-6 μm with specific mass ratio, the conductive paint satisfies the following formula (1): 100≤X1+X2≤260···(1), X1=(the average particle size of conductive powder (B1) / the tap density of conductive powder (B1))×(the content of conductive powder (B1) relative to the total mass of conductive powder (B)), X2=(the average particle size of conductive powder (B2) / the tap density of conductive powder (B2))×(the content of conductive powder (B2) relative to the total mass of conductive powder (B)).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to conductive coatings and circuit forming bodies.

[0002] This application claims priority to Japanese Special Application No. 2022-073168, filed on April 27, 2022, the contents of which are incorporated herein by reference. Background Technology

[0003] In recent years, efforts to popularize devices requiring flexibility or stretchability, such as wearable devices, flexible printed circuit boards, or displays, have become increasingly active. Typically, these devices are formed by coating a flexible or stretchable substrate with a conductive coating containing conductive particles and binder resin, but sometimes the coating film formed by the conductive coating is required to be stretchable.

[0004] As a conductive component with flexible wiring, for example, Patent Document 1 discloses a conductive component having wiring formed by drying a conductive paste of polyurethane dispersion and conductive particles and a plastic substrate.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 2012-54192 Summary of the Invention

[0008] (a) Technical problems to be solved

[0009] However, if the coating film formed by existing conductive coatings is repeatedly stretched or contracted, it may break or the resistance value may increase, thus posing a problem with the stability of the resistance.

[0010] The purpose of this invention is to provide a conductive coating that can form a coating film with excellent durability even after repeated stretching and contraction and a small rate of change in resistance.

[0011] (II) Technical Solution

[0012] The present invention has the following aspects.

[0013] [1] A conductive coating comprising a silicone resin (A) and a conductive powder (B),

[0014] The mass ratio (A / B) of the silicone resin (A) to the conductive powder (B) is 10 / 90 to 35 / 65.

[0015] The conductive powder (B) comprises flake-shaped conductive powder (B1) with an average particle size of 1-7 μm and amorphous conductive powder (B2) with an average particle size of 1-6 μm.

[0016] The mass ratio (B1 / B2) of the conductive powder (B1) to the conductive powder (B2) is 40 / 60 to 90 / 10.

[0017] The conductive coating satisfies the following formula (1):

[0018] 100≤X1+X2≤260 (1)

[0019] X1 = (Average particle size of conductive powder (B1) / Tap density of conductive powder (B1)) × (Conductive powder (B1) content relative to the total mass of conductive powder (B))

[0020] X2 = (Average particle size of conductive powder (B2) / Tap density of conductive powder (B2)) × (Conductive powder (B2) content relative to the total mass of conductive powder (B)).

[0021] [2] According to the conductive coating of [1], wherein the silicone resin (A) comprises a curing silicone resin, preferably comprising at least one of an addition reaction curing silicone resin and a condensation reaction curing silicone resin.

[0022] [3] According to the conductive coating of [2], wherein the silicone resin (A) comprises the addition-curing silicone resin,

[0023] The conductive coating further comprises one or more catalysts selected from platinum-based metal catalysts, rhodium-based metal catalysts, palladium-based metal catalysts, cobalt-based metal catalysts, nickel-based metal catalysts, and iron-based metal catalysts.

[0024] [4] The conductive coating according to any one of [1] to [3], wherein the conductive powder (B1) and the conductive powder (B2) respectively contain one or more of the following: gold, silver, copper, platinum, nickel, graphite and substances composed of two or more elements (e.g., alloys, substances made by coating metal with metal or resin).

[0025] [5] The conductive coating according to any one of [1] to [4], wherein the average particle size of the conductive powder (B1) is 1.5 to 6.7 μm, more preferably 2 to 6.5 μm, and even more preferably 2 to 5 μm.

[0026] [6] The conductive coating according to any one of [1] to [5], wherein the average particle size of the conductive powder (B2) is 1.5 to 5.5 μm, more preferably 2 to 5.5 μm, and even more preferably 2.5 to 5 μm.

[0027] [7] The conductive coating according to any one of [1] to [6], wherein the mass ratio (A / B) of silicone resin (A) to conductive powder (B) is 15 / 85 to 30 / 70, more preferably 15 / 85 to 25 / 75.

[0028] [8] The conductive coating according to any one of [1] to [7], wherein the total content of the silicone resin (A) and the conductive powder (B) relative to the total mass of the conductive coating is 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and particularly preferably 100% by mass.

[0029] [9] The conductive coating according to any one of [1] to [8], wherein the mass ratio (B1 / B2) is 45 / 55 to 85 / 15, more preferably 45 / 55 to 80 / 20.

[0030]

[10] The conductive coating according to any one of [1] to [9], wherein the total content of the conductive powder (B1) and the conductive powder (B2) relative to the total mass of the conductive powder (B) is 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably 100% by mass.

[0031]

[11] The conductive coating according to any one of [1] to

[10] , wherein X1+X2 is 120 to 250, more preferably 130 to 210.

[0032]

[12] A circuit forming body, wherein the circuit forming body is formed by forming a circuit on a substrate using a coating film, said coating film being a coating film obtained using any one of the conductive coatings described in [1] to

[11] .

[0033] (III) Beneficial Effects

[0034] According to the present invention, a conductive coating can be provided, which can form a coating film with excellent durability even with repeated stretching and contraction and a small rate of change in resistance. Attached Figure Description

[0035] Figure 1 A perspective view of a circuit formation according to one embodiment of the present invention is shown schematically. Detailed Implementation

[0036] The following definitions of terms apply to the specification and claims of this application.

[0037] "Conductivity" is a term distinct from "insulation" in the usual sense, indicating that for circuit patterns, a resistance value of less than 150Ω is preferred.

[0038] "Coating film" refers to a coating film formed by the conductive coating material of the present invention.

[0039] The "~" symbol, which indicates a range of values, includes the values ​​listed before and after it, in the manner of setting the lower and upper limits.

[0040] The numerical ranges of content, various physical properties, and morphological values ​​disclosed in this specification can be arbitrarily combined with their lower and upper limits to form new numerical ranges.

[0041] Conductive coatings

[0042] One embodiment of the conductive coating of the present invention comprises a silicone resin (A) and a conductive powder (B) as shown below.

[0043] As long as it does not impair the effects of the present invention, the conductive coating may further include components other than silicone resin (A) and conductive powder (B) (hereinafter also referred to as "arbitrary components").

[0044] <Silicone Resin (A)>

[0045] Silicone resin (A) is a resin with excellent durability and flexibility. Among silicone resins (A), cured silicone resins are preferred.

[0046] Examples of curable silicone resins include addition reaction curable silicone resins, condensation reaction curable silicone resins, free radical reaction curable silicone resins, and UV or electron beam curable silicone resins. Among these, addition reaction curable silicone resins and condensation reaction curable silicone resins are preferred, and addition reaction curable silicone resins are more preferred, considering that they can form not only thin films but also thick films, and that the film thickness can be easily adjusted according to the required application.

[0047] Silicone resin (A) can be used alone or in combination with two or more other types.

[0048] Addition-cured silicone resins are structures formed by the cross-linking of functional groups in two organopolysiloxanes through addition reactions.

[0049] Condensation-cured silicone resins are structures formed by the condensation reaction bonding and cross-linking of functional groups from two organopolysiloxanes, or between organopolysiloxanes and functional groups from silicon compounds such as silica or silanes.

[0050] As a silicone resin (A), commercially available products can be used.

[0051] Commercially available products that are addition-curable silicone resins include, for example, those manufactured by Shin-Etsu Chemical Co., Ltd. under the names "KE-1820" and "KE-1823"; those manufactured by Momentive Performance Materials Japan LLC under the names "TSE-3221", "TSE-3250", and "TSE-3251"; those manufactured by Dow Toray Co., Ltd. under the names "SE-1750" and "SE-4450"; and those manufactured by wacker asahikasei silicone co., Ltd. under the names "SEMICOSIL 987 GR", "SEMICOSIL 988 / 1K GRAY", and "SEMICOSIL 989 / 1K".

[0052] Commercially available products that are condensation reaction-cured silicone resins include, for example, products manufactured by Shin-Etsu Chemical Co., Ltd. under the names "KE-441", "KE-471", and "KE-47"; products manufactured by Momentive Performance Materials Japan LLC under the names "TSE-387" and "TSE-397"; and products manufactured by Dow Toray Co., Ltd. under the names "SE-917G", "SE-9186", and "SE-9184".

[0053] When using an addition-curing silicone resin as silicone resin (A), it is preferable to use a catalyst in conjunction to promote the addition reaction.

[0054] Examples of catalysts include platinum-based metal catalysts, rhodium-based metal catalysts, palladium-based metal catalysts, cobalt-based metal catalysts, nickel-based metal catalysts, and iron-based metal catalysts. Among these, platinum-based metal catalysts are preferred due to their widest applicability and ease of further increasing the rate of addition reactions.

[0055] A single catalyst can be used, or two or more catalysts can be used simultaneously.

[0056] <Conductive Powder (B)>

[0057] The conductive powder (B) comprises flake-shaped conductive powder (B1) with an average particle size of 1 to 7 μm and amorphous conductive powder (B2) with an average particle size of 1 to 6 μm. By including the flake-shaped conductive powder (B1) and the amorphous conductive powder (B2) in the conductive powder (B), a coating film with excellent durability even after repeated stretching and contraction and a small rate of change in resistivity can be formed.

[0058] As long as it does not impair the effects of the present invention, the conductive powder (B) may further include conductive powder other than conductive powder (B1) and conductive powder (B2) (hereinafter also referred to as "conductive powder (B3)").

[0059] (Conductive powder (B1))

[0060] Conductive powder (B1) is a flake-shaped conductive powder with an average particle size of 1~7μm. The average thickness of the flakes is typically 1 / 10 to 1 / 2 of its average particle size.

[0061] Conductive powder (B1) imparts conductivity to the coating.

[0062] As a conductive powder (B1), there are no particular restrictions as long as it can be used in conductive coatings. Examples include metals such as gold, silver, copper, platinum, and nickel, as well as graphite. Among these, silver is preferred due to its excellent conductivity and resistance to oxidation.

[0063] Furthermore, the conductive powder (B1) can also be a powder composed of two or more elements, such as an alloy, or a powder formed by coating a metal or resin with the metals listed above. Among these, from the perspective of excellent conductivity and resistance to oxidation, a powder formed by coating a metal or resin other than silver with silver is preferred.

[0064] Conductive powder (B1) can be used alone or in combination with two or more.

[0065] In addition, in this invention, "sheet-like" can be replaced with scale-like, flat, plate-like, or thin sheet-like.

[0066] The average particle size of the conductive powder (B1) is 1~7 μm, preferably 1.5~6.7 μm, more preferably 2~6.5 μm, and even more preferably 2~5 μm. By making the average particle size of the conductive powder (B1) at or above the above-mentioned lower limit value, conductivity can be well maintained. By making the average particle size of the conductive powder (B1) at or below the above-mentioned upper limit value, the durability of the coating film remains excellent even with repeated stretching and contraction.

[0067] The average particle size of the conductive powder (B1) is a value obtained by means of the following method: the arithmetic mean particle size calculated from the volume distribution measured by laser diffraction scattering particle size distribution measurement method is used as the average particle size of the conductive powder (B1). Alternatively, for powders with recorded values, these recorded values ​​can be used as a simplified measurement method to determine the average particle size of the conductive powder (B1).

[0068] (Conductive powder (B2))

[0069] The conductive powder (B2) is an amorphous conductive powder with a diameter of 1~6μm.

[0070] Conductive powder (B2) imparts conductivity to the coating film.

[0071] As a conductive powder (B2), there are no particular limitations as long as it can be used in conductive coatings. Examples include metals such as gold, silver, copper, platinum, and nickel, as well as graphite. Among these, silver is preferred due to its excellent conductivity and resistance to oxidation.

[0072] Furthermore, the conductive powder (B2) can be composed of two or more elements, such as an alloy, or a powder made by coating a metal or resin with the metals listed above. Among these, from the perspective of excellent conductivity and resistance to oxidation, a powder made by coating a metal or resin other than silver with silver is preferred.

[0073] Conductive powder (B2) can be used alone or in combination with two or more.

[0074] Furthermore, in this invention, "amorphous" refers to a shape other than sheet-like, indicating a state in which two or more of various shapes, such as spherical, cubic, needle-like, bead-like, or shapes with protrusions on the surface like konpeito, exist in a mixture and the shape cannot be defined; an aggregate formed by the aggregation of primary particles containing one or more shapes selected from spherical, cubic, needle-like, bead-like, or shapes with protrusions on the surface like konpeito.

[0075] The average particle size of the conductive powder (B2) is 1 to 6 μm, preferably 1.5 to 5.5 μm, more preferably 2 to 5.5 μm, and even more preferably 2.5 to 5 μm. If the average particle size of the conductive powder (B2) is above the lower limit mentioned above, conductivity can be well maintained. Furthermore, the durability of the coating film remains excellent even with repeated stretching and contraction. If the average particle size of the conductive powder (B2) is below the upper limit mentioned above, the durability of the coating film remains excellent even with repeated stretching and contraction.

[0076] The average particle size of the conductive powder (B2) is a value obtained by means of the following method: the arithmetic mean particle size calculated from the volume distribution measured by laser diffraction scattering particle size distribution determination method is taken as the average particle size of the conductive powder (B2). Alternatively, for powders with recorded values, the recorded values ​​can be used as a simplified measurement method to determine the average particle size of the conductive powder (B2).

[0077] (Conductive powder (B3))

[0078] The conductive powder (B3) is a conductive powder other than the conductive powder (B1) and conductive powder (B2).

[0079] Examples of conductive powders (B3) include flake-shaped conductive powders with an average particle size greater than 7 μm, amorphous conductive powders with an average particle size greater than 6 μm, and shaped conductive powders such as spherical powders.

[0080] Conductive powder (B3) imparts conductivity to the coating.

[0081] As a conductive powder (B3), there are no particular limitations as long as it can be used in conductive coatings. Examples include metals such as gold, silver, copper, platinum, and nickel, as well as graphite. Among these, silver is preferred due to its excellent conductivity and resistance to oxidation.

[0082] Furthermore, the conductive powder (B3) can be composed of two or more elements, such as an alloy, or a powder made by coating a metal or resin with the metals listed above. Among these, from the perspective of excellent conductivity and resistance to oxidation, a powder made by coating a metal or resin other than silver with silver is preferred.

[0083] Conductive powder (B3) can be used alone or in combination with two or more.

[0084] <Any ingredient>

[0085] As an arbitrary component, the following components that can be used in existing known conductive coatings can be listed, such as organic solvents, binder resins other than silicone resin (A), dispersants, surface conditioners, thixotropic agents, bonding agents, resin modifiers, etc.

[0086] Any ingredient can be used alone or in combination with two or more ingredients.

[0087] Of the aforementioned components, insulating components that remain as solid components during coating film formation can reduce the conductivity of the coating film, and are therefore preferably not present. Furthermore, when the conductive coating contains an addition-reactive silicone resin as silicone resin (A), it is preferable that it does not substantially contain impurities such as sulfur, which act as curing inhibitors.

[0088] "Substantially not containing" means that, except by accident, it is not actively mixed with insulating components or impurities such as sulfur that act as curing hindrances.

[0089] If the conductive coating contains organic solvents, the viscosity can be easily adjusted.

[0090] As an organic solvent, a solvent that can dissolve silicone resin (A) is preferred, such as a mixture of petroleum-based aliphatic hydrocarbon solvents or petroleum-based aromatic solvents, or a single substance such as toluene, diethylbenzene, naphthane, or dodecane.

[0091] Organic solvents can be used alone or in combination with two or more.

[0092] Other adhesive resins besides silicone resin (A) (hereinafter also referred to as "other adhesive resins") include, for example, polyester resins, phenoxy resins, polyamide resins, polyamide-imide resins, polyimide resins, polyurethane resins, acrylic resins, polystyrene, styrene-acrylic resins, styrene-butadiene copolymers, epoxy resins, phenolic resins, polyether resins, polycarbonate resins, alkyd resins, polysulfone resins, polyethersulfone resins, vinyl chloride-vinyl acetate copolymers, ethylene-vinyl acetate copolymers, fluorinated resins, and resins modified with organosilicon.

[0093] Other adhesive resins can be used alone or in combination with two or more.

[0094] <Content-to-mass ratio>

[0095] The mass ratio (A / B) of silicone resin (A) to conductive powder (B) is 10 / 90 to 35 / 65, preferably 15 / 85 to 30 / 70, and more preferably 15 / 85 to 25 / 75. If the mass ratio (A / B) is 10 / 90 or higher, the coating film maintains excellent durability even with repeated stretching and contraction. If the mass ratio (A / B) is 35 / 65 or lower, conductivity is well maintained. Furthermore, the coating film maintains excellent durability even with repeated stretching and contraction.

[0096] Furthermore, when using an addition-reaction-curing silicone resin as silicone resin (A), and simultaneously using both an addition-reaction-curing silicone resin and a catalyst, the mass of silicone resin (A) used to calculate the mass ratio (A / B) and the content of silicone resin (A) described below also include the mass of the catalyst. Moreover, when using both an addition-reaction-curing silicone resin and a catalyst, the content of the catalyst is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the addition-reaction-curing silicone resin.

[0097] The total content of silicone resin (A) and conductive powder (B) relative to the total mass of the conductive coating is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and may also be 100% by mass. That is, the conductive coating may consist only of silicone resin (A) and conductive powder (B).

[0098] The mass ratio (B1 / B2) of conductive powder (B1) to conductive powder (B2) is 40 / 60 to 90 / 10, preferably 45 / 55 to 85 / 15, and more preferably 45 / 55 to 80 / 20. If the mass ratio (B1 / B2) is 40 / 60 or higher, the coating film exhibits excellent durability even with repeated expansion and contraction, and the rate of change in the coating film's resistivity is small. If the mass ratio (B1 / B2) is 90 / 10 or lower, the coating film also exhibits excellent durability even with repeated expansion and contraction.

[0099] The total content of conductive powder (B1) and conductive powder (B2) relative to the total mass of conductive powder (B) is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and may also be 100% by mass. That is, conductive powder (B) may consist only of conductive powder (B1) and conductive powder (B2).

[0100] <Formula (1)>

[0101] Conductive coatings satisfy the following equation (1):

[0102] 100≤X1+X2≤260 (1)

[0103] X1 = (Average particle size of conductive powder (B1) / Tap density of conductive powder (B1)) × (Conductive powder (B1) content relative to the total mass of conductive powder (B))

[0104] X2 = (Average particle size of conductive powder (B2) / Tap density of conductive powder (B2)) × (Conductive powder (B2) content relative to the total mass of conductive powder (B))

[0105] X1+X2 is 100~260, preferably 120~250, and more preferably 130~210. If X1+X2 is above the lower limit above, the coating film maintains excellent durability even with repeated stretching and contraction, and the rate of change of the coating film's resistance is small. If X1+X2 is below the upper limit above, the coating film maintains excellent durability even with repeated stretching and contraction, and the rate of change of the coating film's resistance is small.

[0106] The tap density of conductive powder (B1) and conductive powder (B2) can be determined according to the method of JIS Z2512:2012. Alternatively, for powders with recorded values, the recorded values ​​can be used as a simplified measurement value as the tap density of conductive powder (B1) or conductive powder (B2).

[0107] <Manufacturing Method>

[0108] The conductive coating is obtained by mixing the aforementioned silicone resin (A) and conductive powder (B) with any other required components.

[0109] For mixing, a mixer such as a rolling mill or a planetary mixer can be used.

[0110] <Effects>

[0111] The conductive coating of the present embodiment described above satisfies the above formula (1) and contains silicone resin (A) and conductive powder (B) in a specific ratio. The conductive powder (B) contains flake-shaped conductive powder (B1) and amorphous conductive powder (B2) with a specific average particle size in a specific ratio. Therefore, it is possible to form a coating with excellent durability and a small rate of change in resistance value even if the coating is repeatedly stretched and stretched.

[0112] <Uses>

[0113] Applications of the conductive coating of this embodiment include circuits for electronic components. Specifically, applications include touch panel circuits, flexible substrates, and wearable devices. The conductive coating of this embodiment is capable of forming a film with excellent durability even after repeated stretching and contraction and a small rate of change in resistance, making it particularly suitable for applications requiring flexibility or stretchability, such as flexible substrates and wearable devices.

[0114] [Circuit Formulation]

[0115] In one embodiment of the present invention, a circuit form is formed by forming a circuit on a substrate using a coating film, wherein the coating film is a coating film obtained using the conductive coating of the present invention described above (hereinafter also referred to as a "conductive coating film"). That is, the circuit form has a substrate and a circuit formed on the substrate, the circuit being formed by using the conductive coating of the present invention.

[0116] Figure 1 An example of the circuit formation of this embodiment is shown in the figure. Figure 1 The circuit form 10 shown has a substrate 11 and a circuit 12 formed on the substrate 11.

[0117] As substrate 11, existing known substrates used as wiring boards can be used, such as substrates made of inorganic materials such as glass substrates, ceramic substrates, and silicone substrates; substrates made of organic materials, etc.

[0118] Examples of organic materials include: polyesters such as polyethylene terephthalate and polyethylene naphthalate; organosilicones such as polydimethylsiloxane, polydiphenylpolysiloxane, and polyfluorosiloxane; urethanes such as thermoplastic polyurethane elastomers; polyimides; polyphenylene sulfide; polyolefins such as polyethylene and polypropylene; polyamides; polystyrene; acrylic acid; polyvinyl alcohol; ethylene propylene diene; and epoxides. Among these, substrates formed of organosilicon (organosilicon substrates) are preferred due to their good adhesion to silicone resins in conductive coatings.

[0119] The thickness of the substrate 11 can be appropriately set according to the application of the circuit form 10, and is preferably 20 to 600 μm. If the thickness of the substrate 11 is within the above range, it is easy to form a circuit form 10 with good flexibility and durability.

[0120] There is no particular limitation on the method of forming the circuit 12 on the substrate 11. For example, the following method can be listed: the conductive coating of the present invention is applied to the substrate 11 in such a way as to form the desired circuit pattern, and then dried to form the circuit 12 composed of the coating film.

[0121] That is, as one embodiment of the manufacturing method of the circuit forming body 10, the following steps are included: a pattern forming step of applying the conductive coating of the present invention onto the substrate 11 to form a circuit pattern; and a drying step of drying the circuit pattern.

[0122] Methods for applying conductive coatings include, for example, screen printing, gravure printing, offset printing, roller coating, bar coating, drop coating, dipping, transfer printing, inkjet printing, and aerosol jetting.

[0123] The drying temperature is preferably 70~160°C.

[0124] The drying time is preferably 2 to 60 minutes.

[0125] The circuit formed by the embodiment described above, having a circuit formed by a coating obtained using the conductive coating of the present invention, exhibits excellent durability even with repeated stretching and contraction, and a small rate of change in resistance. Therefore, the circuit formed by the embodiment is particularly suitable for applications requiring flexible substrates and wearable devices.

[0126] Example

[0127] The present invention will be described in more detail below through embodiments, but the present invention is not limited thereto.

[0128] In addition, Examples 2-8, 10, 14, 16-19, and 22-27 below are examples, and Examples 1, 9, 11-13, 15, 20, 21, 28, and 29 are comparative examples.

[0129] The materials used in each example are as follows.

[0130] [Material]

[0131] • A-1: ​​Addition reaction curing silicone resin (manufactured by Wacker Asahikasei Silicone Co., Ltd., product name "SEMICOSIL 989 / 1K", containing platinum catalyst).

[0132] • B1-1: Flake-shaped silver powder (manufactured by Tokuryu Chemical Research Institute Co., Ltd., product name "TC-20V", average particle size: 3.6μm, tap density: 3g / cm³) 3 ).

[0133] • B1-2: Flake-shaped silver powder (manufactured by Ames Goldsmith Corporation, product name "SF70M", average particle size: 2.1 μm, tap density: 3.15 g / cm³). 3 ).

[0134] • B1-3: Flake-shaped silver powder (manufactured by Tokureki Chemical Research Institute Co., Ltd., product name "TC-506", average particle size: 6.7μm, tap density: 5.5g / cm³) 3 ).

[0135] • B1-4: Flake-shaped silver powder (manufactured by Tokuryu Chemical Research Institute Co., Ltd., product name "TC-25A", average particle size: 7.7μm, tap density: 3.5g / cm³) 3 ).

[0136] • B2-1: Amorphous silver powder (manufactured by YOKOSAWA CHEMICAL. Co. Ltd., product name "Y-AF-K", average particle size: 3μm, tap density: 1.15g / cm³) 3 ).

[0137] • B2-2: Amorphous silver powder (aggregate) (manufactured by Ames Goldsmith Corporation, product name "SPK-1", average particle size: 3μm, tap density: 0.75g / cm³) 3 ).

[0138] • B2-3: Amorphous silver powder (manufactured by Ames Goldsmith Corporation, product name "SPG", average particle size: 5.36 μm, tap density: 1 g / cm³) 3 ).

[0139] • B2-4: Amorphous silver powder (aggregate) (manufactured by Ames Goldsmith Corporation, product name "SPI", average particle size: 4.54 μm, tap density: 1.1 g / cm³) 3 ).

[0140] • B2-5: Amorphous silver powder (manufactured by Tokuryu Chemical Research Institute Co., Ltd., product name "C-34", average particle size: 0.34 μm, tap density: 2.25 g / cm³) 3 ).

[0141] • B2-6: Amorphous silver powder (aggregate) (manufactured by Tokuryu Chemical Research Institute Co., Ltd., product name "E-20", average particle size: 10.8 μm, tap density: 2 g / cm³) 3 ).

[0142] • B2-7: Amorphous silver powder (manufactured by YOKOSAWA CHEMICAL. Co. Ltd., product name "Y-AE-K", average particle size: 2μm, tap density: 1.3g / cm³) 3 ).

[0143] • B2-8: Amorphous silver powder (manufactured by MITSUI MINING & SMELTING CO.,LTD., product name "SPN10JS", average particle size: 2μm, tap density: 5.3g / cm³) 3 ).

[0144] • B3-1: Spherical silver powder (manufactured by DOWA ELECTRONICS MATERIALS CO., LTD., average particle size: 1.6 μm, tap density: 3.8 g / cm³) 3 ).

[0145] [Examples 1~29]

[0146] According to the proportions shown in Tables 1-3, a total of 100 parts by mass of silicone resin (A) and conductive powder (B) were mixed and dispersed in 11 parts by mass of solvent (dodecane) to obtain a conductive coating with a solid content concentration of 90% by mass. Additionally, blank columns in Tables 1-3 indicate that this component was not incorporated.

[0147] Conductive coating was applied to a substrate made of silicone material with a width of 15 mm, a length of 70 mm, and a thickness of 100 μm by screen printing to form a pattern with a width of 1 mm, a length of 50 mm, and a thickness of 20 μm. Then, it was dried at 160 °C for 60 minutes and cured to produce a test piece with circuit patterns formed on the substrate.

[0148] The conductivity, rate of change of resistance, and durability of the obtained test pieces were evaluated in the following ways. The results are shown in Tables 1-3.

[0149] (1) Evaluation of conductivity

[0150] Use a digital multimeter (manufactured by ADC CORPORATION) to measure the resistance between the two ends of the circuit pattern along its length, and evaluate the conductivity according to the following evaluation criteria.

[0151] A: The resistance value is less than 10Ω.

[0152] B: The resistance value is above 10Ω and less than 150Ω.

[0153] C: Resistance value is 150Ω or higher.

[0154] (2) Evaluation of the rate of change of resistance value

[0155] A circuit pattern with an initial length of 50 mm was stretched to 60 mm and then returned to its initial length of 50 mm. This stretching and contraction process was repeated 100 times at a stretching / contraction speed of 500 mm / min to conduct a resistance change test. Then, the resistance value between the two ends of the circuit pattern along its length was measured, and the rate of change of resistance was calculated as (([resistance value after the 100th stretching / contraction] - [resistance value before the test]) / [resistance value before the test] × 100 (%)). The conductivity was evaluated according to the following evaluation criteria.

[0156] A: The rate of change is less than 2000%.

[0157] B: The rate of change is above 2000% and less than 4000%.

[0158] C: The rate of change is over 4000%.

[0159] (3) Durability evaluation

[0160] Conduct the resistance change test in the same manner as in (2). Calculate the difference between the rate of change of resistance after the 10th expansion and the rate of change of resistance after the 100th expansion ([rate of change of resistance after the 100th expansion] - [rate of change of resistance after the 10th expansion] (%), and evaluate the conductivity according to the following evaluation criteria.

[0161] A: The difference in the rate of change is less than 20%.

[0162] B: The difference in the rate of change is greater than 20% and less than 40%.

[0163] C: The difference in the rate of change is over 40%.

[0164] [Table 1]

[0165]

[0166] [Table 2]

[0167]

[0168] [Table 3]

[0169]

[0170] The conductive coatings obtained in Examples 2-8, 10, 14, 16-19, and 22-27 can form a coating film with excellent conductivity, excellent durability even with repeated stretching and contraction, and a small rate of change in resistance.

[0171] In contrast, the coating film formed by the conductive coating of Example 1, in which the mass ratio (B1 / B2) of conductive powder (B1) to conductive powder (B2) is 95 / 5, has poor durability.

[0172] The coating film formed by the conductive coating of Example 9, which contains flake-shaped silver powder with an average particle size of 7.7 μm and does not contain flake-shaped conductive powder (B1) with an average particle size of 1 to 7 μm, has poor durability.

[0173] The resistance of the coating film formed by the conductive coating in Example 11, where X1+X2 is 281, changed significantly due to repeated expansion and contraction. Furthermore, its durability was poor.

[0174] The coating film formed by the conductive coating of Example 12, which contains amorphous silver powder with an average particle size of 0.34 μm and does not contain amorphous conductive powder (B2) with an average particle size of 1 to 6 μm, has poor conductivity and durability.

[0175] The coating film formed by the conductive coating of Example 13, which contains amorphous silver powder with an average particle size of 10.8 μm and does not contain amorphous conductive powder (B2) with an average particle size of 1~6 μm, has poor durability.

[0176] The resistivity of the coating film formed by the conductive coating in Example 15, where X1+X2 is 92.82, changed significantly due to repeated expansion and contraction. Furthermore, its durability was poor.

[0177] The resistivity of the coating film formed by the conductive coating of Example 20, in which the mass ratio (B1 / B2) of conductive powder (B1) and conductive powder (B2) is 35 / 65, changed significantly due to repeated expansion and contraction. Furthermore, its durability was poor.

[0178] The coating film formed by the conductive coating of Example 21, in which the mass ratio (A / B) of silicone resin (A) to conductive powder (B) is 8 / 92, has poor durability.

[0179] The conductive coating of Example 28, in which the mass ratio (A / B) of silicone resin (A) and conductive powder (B) is 40 / 60, has poor conductivity and durability.

[0180] The resistivity of the conductive coating film formed by Example 29, which uses spherical conductive powder (B3) with an average particle size of 1.6 μm instead of amorphous conductive powder (B2) with an average particle size of 1~6 μm, changed significantly due to repeated stretching and contraction. Furthermore, its durability was poor.

[0181] Industrial applicability

[0182] The conductive coating of the present invention can form a coating film with excellent durability even with repeated stretching and contraction and a small rate of change in resistance value. Therefore, it is useful as a coating for forming circuits of electronic components such as touch panel circuits, flexible substrates, and wearable devices.

[0183] Explanation of reference numerals in the attached figures

[0184] 10: Circuit form; 11: Substrate; 12: Circuit.

Claims

1. A conductive coating, wherein, The conductive coating comprises silicone resin (A) and conductive powder (B). The mass ratio (A / B) of the silicone resin (A) to the conductive powder (B) is 10 / 90 to 35 / 65. The conductive powder (B) comprises flake-shaped conductive powder (B1) with an average particle size of 1-7 μm and amorphous conductive powder (B2) with an average particle size of 1-6 μm. The mass ratio (B1 / B2) of the conductive powder (B1) to the conductive powder (B2) is 40 / 60 to 90 / 10, and the conductive coating satisfies the following formula (1): 100≤X1+X2≤260···(1) X1 = (Average particle size of conductive powder (B1) / Tap density of conductive powder (B1)) × (Conductive powder (B1) content relative to the total mass of conductive powder (B)) X2 = (Average particle size of conductive powder (B2) / Tap density of conductive powder (B2)) × (Conductive powder (B2) content relative to the total mass of conductive powder (B)).

2. A circuit form, wherein, The circuit is formed by forming a circuit on a substrate using a coating film, wherein the coating film is obtained using the conductive coating material as described in claim 1.

Citation Information

Patent Citations

  • Conductive member with elastic wiring

    JP2012054192A

  • Weight type filling apparatus

    JP2022073168A

  • Electroconductive silver paste

    CN107112069A

  • Electroconductive paste

    CN112912971A